Application of Computational Fluid Dynamics (CFD) for Simulation of Acid Mine Drainage Generation and Subsequent Pollutants Transportation through Groundwater Flow Systems and Rivers - Ardejani, Faramarz Doulati; Baafi, Ernest; Panahi, Kumars Seif; Singh, Raghu Nath; Shokri, Behshad Jodeiri (IntechOpen, 2011)
None